APPLICATION OF BENENG TARO STARCH EDIBLE FILM WITH THE ADDITION OF PINEAPPLE EXTRACT IN PINEAPPLE DODOL - Trivira Wulansuci; Yelmira Zalfiatri; Yanti Nopiani; Chandra Gunawan; Anne Mudya Yolanda (SAGU, 2026)
The objective of this study was to determine the optimal combination of beneng taro starch and pineapple peel extract in the formulation of edible films for pineapple dodol packaging. As a semi-moist food,  pineapple dodol is highly susceptible to spoilage, therefore the application of an edible film coating serves  as a strategic solution to extend its shelf life. This research evaluates how varying these components affects the functional characteristics of the film to ensure maximum protection for the product. The experimental design used was a completely randomized factorial design with 2 factors, namely the addition of taro starch (2 g, 3 g, 4 g, 5 g) and the addition of pineapple peel extract (1%, 2%, 3% v/v), with 3 repetitions. Parameters observed were edible film thickness, water vapor transmission rate (WVTR), water resistance, moisture content of the dodol, total plate count (TPC), and sensory aroma evaluation. Data were statistically using Analysis of Variance (ANOVA) and continued with Duncan’s Multiple Range Test (DMRT) at the 5% level. Results indicated an interaction effect between starch and extract on the WVTR  and water resistance of the edible film.  The individuals treatments significantly affected thickness, WVTR, water resistance, moisture, TPC, and aroma scores. The best treatment was P5K3 (5 g of beneng taro starch and 3% pineapple peel extract) with criteria of thickness 0.221 mm, WVTR 6.67 g/m²/hour, percentage swelling water resistance 81.71%, moisture content 20.50%, TPCS 3.52 log CFU/g, and descriptive aroma of pineapple dodol 1.33 (not rancid) lasts until the 6th day.